Property Industry Financing Behaviour Model for Low-Income Communities (MBR) in Langkat Regency - Irawan; Abdi Setiawan; Surya Asih; Nurul Ardika; Priska Gulo (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2024)
This study aims to formulate and estimate three main models to obtain an overview of the demand for property credit at the Low-Income Community (MBR) level. The empirical model used for estimation is Structural Equation Modeling (SEM). The design of this study is quantitative based on explanatory research. The research data were obtained from distributing questionnaires with a sample of 96 respondents. The results of this study prove that Financing Behavior affects Financing Supply. Specifically, the research findings conclude that Financing Behavior can increase Financing Supply. The second hypothesis test proves that Financing Behavior affects Financing Demand. Specifically, the research findings conclude that Financing Behavior can increase Financing Demand. The third hypothesis test proves that planning from Financing Expectations influence on Financing Supply. Hypothesis testing s The fourth proves that planning from Financing Expectations does not affect Financing Demand . Specifically , the research findings​ m e n y o n g​​ that​​ Financing Expectations have not been able to increase Financing Demand.